MO462: Change in KDIGO Kidney Risk Category With Semaglutide Treatment—A Post Hoc Analysis of the Sustain 6 Trial. (3rd May 2022) - Tuttle, Katherine; Bain, Stephen C; Cherney, David; Lawson, Jack; Rasmussen, Søren; Vrhnjak, Blaz; Khunti, Kamlesh
Abstract: BACKGROUND AND AIMS: Glucagon-like peptide-1 receptor agonists, such as semaglutide, have been associated with reductions in albuminuria, and may preserve estimated glomerular filtration rate (eGFR) in people with type 2 diabetes (T2D). However, it has not been explored whether treatment with semaglutide affects a person's chronic kidney disease (CKD) risk category. The Kidney Disease: Improving Global Outcomes (KDIGO) risk category classification is a validated approach for defining the likelihood of CKD and cardiovascular (CV) disease progression, based on eGFR and urinary albumin-to-creatinine ratio (UACR). The aim of this analysis was to determine whether treatment with once-weekly (OW) semaglutide resulted in improvements in KDIGO risk category compared with placebo. METHOD: The proportion of subjects with T2D moving to a lower KDIGO risk category, remaining in the same category or moving to a higher risk category between baseline and 2 years on treatment with OW subcutaneous semaglutide versus placebo was assessed post hoc using SUSTAIN 6 (NCT01720446) CV outcomes trial data. The endpoints were assessed for the overall population and by baseline KDIGO risk category (low, moderate, high and very high). Sensitivity analyses were conducted to investigate the contributions of UACR and eGFR to change in risk category. RESULTS: Data from 2804 of the 3297 subjects randomized in SUSTAIN 6 were available for this post hoc analysis. At 2 years, in the overall population, subjects receiving OW semaglutide were more likely to move to a lower risk category ( n = 183; 13.0%) than subjects receiving placebo ( n = 114; 8.2%); odds ratio (OR; semaglutide versus placebo) 1.69 [95% confidence interval (CI) 1.32; 2.16, P < 0.0001) (Figure ). Conversely, subjects receiving OW semaglutide were less likely to move to a higher risk category ( n = 254; 18.1%) than those receiving placebo ( n = 330; 23.6%); OR 0.71 (95% CI 0.59;0.86, P = 0.0003) (Figure ). When the data were stratified by baseline KDIGO risk categories, across all categories, greater proportions of subjects receiving semaglutide than placebo moved to a lower risk category and lower proportions of subjects receiving semaglutide than placebo moved to a higher risk category (Figure ). The effects of semaglutide on UACR and eGFR both contributed to the favourable change-in-risk-category profile compared with placebo (Table ). CONCLUSION: Subjects receiving semaglutide versus placebo were more likely to move to a lower KDIGO risk category and less likely to move to a higher risk category, both in the overall population and across KDIGO risk category subgroups. The potential kidney protective effects of semaglutide and the mechanisms underlying these are being investigated in subjects with T2D and CKD in the FLOW and REMODEL trials.